Hospitalization of older adults due to ambulatory care sensitive conditions - Aline Pinto Marques; Dalia Elena Romero Montilla; Wanessa da Silva de Almeida; Carla Lourenço Tavares de Andrade (Universidade de São Paulo, 2014)
OBJECTIVE To analyze the temporal evolution of the hospitalization of older adults due to ambulatory care sensitive conditions according to their structure, magnitude and causes. METHODS Cross-sectional study based on data from the Hospital Information System of the Brazilian Unified Health System and from the Primary Care Information System, referring to people aged 60 to 74 years living in the state of Rio de Janeiro, Souhteastern Brazil. The proportion and rate of hospitalizations due to ambulatory care sensitive conditions were calculated, both the global rate and, according to diagnoses, the most prevalent ones. The coverage of the Family Health Strategy and the number of medical consultations attended by older adults in primary care were estimated. To analyze the indicators' impact on hospitalizations, a linear correlation test was used. RESULTS We found an intense reduction in hospitalizations due to ambulatory care sensitive conditions for all causes and age groups. Heart failure, cerebrovascular diseases and chronic obstructive pulmonary diseases concentrated 50.0% of the hospitalizations. Adults older than 69 years had a higher risk of hospitalization due to one of these causes. We observed a higher risk of hospitalization among men. A negative correlation was found between the hospitalizations and the indicators of access to primary care. CONCLUSIONS Primary healthcare in the state of Rio de Janeiro has been significantly impacting the hospital morbidity of the older population. Studies of hospitalizations due to ambulatory care sensitive conditions can aid the identification of the main causes that are sensitive to the intervention of the health services, in order to indicate which actions are more effective to reduce hospitalizations and to increase the population's quality of life.